Orientação sexual nas escolas: análise dos dizeres dos documentos oficiais do Brasil e da Argentina - Gonzalez, Bruno Martín (2017)
During this dissertation we have analysed the sayings of four (4) discursive cuts out taken from the following documents: 1- Pârametros curriculares- Conteúdos Transversais del Brasil, 2- Nota Técnica 24//2015 de Brasil, 3- Lineamientos Curriculares para la Educación Sexual Integral (ESI) y 4- Ley de ESI 26150/2006. We have aproach theses discursive cut out taking into account the French theory of Discourse Analysis from Pêcheux. The main objective of this research was to make an interpretation of the sayings of the OD (official documents) about the topic on gender and sexuality at schools. Being this, we have worked with concepts that come from this DA orientation, with these concepts we gave an interpretation of the discursive formation that compound the ODs transverse discourse and intradiscourse. Our analysis has been guided for our hypothesis and objectives aiming to reveal possible meaning effects which would be dispersive. Thus, our methodology was based on the analysis of Discourse Cut Out (DC) taken from the ODs previously named. In this DC we understood that, even when the ODs bring a big advance about the topic on gender and sexuality at/in school, they are disperse in their effects, remitting thus to different DFs, such as DF religious, biological, Queer and feminist. In this way, the sayings would remit us to discourses which have conceptions that are hegemonic and historical, when talking about the topic, as well as the discoursive process, too, would remit us to DF pos identitarians.